PENGARUH KOMPETENSI, KOMITMEN DAN MOTIVASI TERHADAP PENDETEKSIAN KECURANGAN PEMBUKUAN DENGAN INTUISI SEBAGAI MODERATING VARIABEL - Asner Haloho (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This research aim to examine the influence of Competence, Commitment, Motivation and Intuition as Moderating Variable of Detection Bookeping Fraud at Auditors in Batam City that is Badan Pemeriksa Keuangan (BPK), Badan Pengawasan Keuangan dan Pembengunan (BPKP) and Public Accountant (KAP). The data taken from questionaires distributed to respondents. Variables in this research is the independent variable (independent) Competence (X1), Commitment (X2) Motivation (X3), and Intuition as Moderating Variable, while the bound variable (dependent) is the Detection Bookeping Fraud (Y). Data were analyzed using multiple linear regression analysis (multiple regretion). The results showed that the Competence, Commitment and Intuition have a positive and significant impact on Detection Bookeping Fraud, while the Motivation of the variables do not have a significant impact on Detection Bookeping Fraud. Value of the coefficient of determination indicates that together the Competence, Commitment, Motivation and Intuition contribute to the dependent variable (quality audit) of 44%, while the remaining 56% are influenced by other outside factor model. Implications of these findings for efforts to realization of a Detection Bookeping Fraud is the need for Improve Competency, Commitment and Motivating to the auditor about the urgency of a Detection Bookeping Fraud in addition to efforts to increase the Intuition auditors.